Controversies and insights into cytokine regulation of neurogenesis and behavior in adult rodents - Sepúlveda-Cuéllar, Rodrigo Daniel; Soria-Medina, Diego Alberto; Cañedo-Solares, Irma; Gómez-Chávez, Fernando; Molina-López, Liliana Monserrat; Cruz-Martínez, María Yolanda; Correa, Dolores (Frontiers in Immunology, 2025)
Adult learning, memory, and social interaction partially depend on neurogenesis in two regions: the hippocampus and the subventricular zone. There is evidence that the immune system is important for these processes in pathological situations, but there is no review of its role in non-pathological or near-physiological conditions. Although further research is warranted in this area, some conclusions can be drawn. Intrusive LyC6hi monocytes and autoreactive CD4+ T cells have a positive impact on neurogenesis and behavior, but the latter are deleterious if specific to external antigens. Mildly activated microglia play a crucial role in promoting these processes, by eliminating apoptotic neuronal progenitors and producing low levels of interleukins, which increase if the cells are activated, leading to inhibition of neurogenesis. Chemokines are poorly studied, but progenitor cells and neurons express their receptors, which appear important for migration and maturation. The few works that jointly analyzed neurogenesis and behavior showed congruent effects of immune cells and cytokines. In conclusion, the immune system components -mostly local- seem of utmost importance for the control of behavior under non-pathological conditions.